EVALUASI PROGRAM PEMBELAJARAN KELAS RANGKAP (PKR) DI COMMUNITY LEARNING CENTER (CLC) - Arman; Haling, Abdul; Arnidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Program evaluation is very important for an educational institution to assess the extent of the success of the program that is being or has been implemented. This study aims to evaluate the implementation of the multigrade teaching program at the Community Learning Center (CLC) United Malacca 3&4 using the context, input, process, and product (CIPP) evaluation model. The subjects in this study were teachers and students of CLC United Malacca 3&4 consisting of 3 teachers, students of class IV, V, and VI each 1 student. This study used a descriptive qualitative method, with data collection techniques through observation, interviews, and documentation. Data validity checking uses source triangulation by comparing data obtained from teachers and students. Data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing. The results showed that the multigrade teaching program at CLC United Malacca 3&4 has been running quite effectively and efficiently although its implementation is still not optimal and needs to be improved. The multigrade teaching program is the most appropriate solution in overcoming the shortage of teachers and the shortage of learning spaces at CLC.